(untitled) (Analysis in Theory and Applications, 2019)
In this paper, we prove a form of the strong comparison principle for a class of fully nonlinear subelliptic operators of the form abla^2_H,sψ + L(·,ψ, abla_Hψ) on the Heisenberg group, which include the CR invariant operators.